1972
DOI: 10.1159/000130186
|View full text |Cite
|
Sign up to set email alerts
|

A 45, XX,5–,13–, dic+ karyotype in a case of cri-du-chat syndrome

Abstract: A 45,XX,5–,13–, dic+ karyotype, verified by autoradiography and fluorescence studies, was found in a nine-year-old patient with typical clinical features of the cri-du-chat syndrome. A dicentric translocation chromosome was present in 34% of about 250 lymphocyte or fibroblast metaphases examined. Twisting in the intercentromeric region, leading to criss-cross separations, might explain the presence in 4% of the cells of a 46, XX,5p– karyotype. Other metaphases showed only one centromere on the translocation ch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
13
1

Year Published

1973
1973
1997
1997

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 41 publications
(15 citation statements)
references
References 6 publications
1
13
1
Order By: Relevance
“…Roberts et al (1977) have suggested that in a dicen tric formed by an acrocentric and a nonacrocentric, the dominant centromere would be that of the non acrocentric. The present findings, as well as those of Niebuhr (1972) and Dewald et al (1979). do not sup port this idea.…”
Section: Discussioncontrasting
confidence: 94%
See 1 more Smart Citation
“…Roberts et al (1977) have suggested that in a dicen tric formed by an acrocentric and a nonacrocentric, the dominant centromere would be that of the non acrocentric. The present findings, as well as those of Niebuhr (1972) and Dewald et al (1979). do not sup port this idea.…”
Section: Discussioncontrasting
confidence: 94%
“…1973;Pallistcr ct al.. 1974;Nakagomc ct al., 1976;Roberts el al., 1977;Daniel et al, 1979); no dicentric was found, and the inactive centromere was always the same in each in dividual. In two other cases (Niebuhr, 1972;Dewald et al, 1979) the translocation chromosome appeared in the same individual as a pscudodicentric with either one or the other centromere inactivated, or, rarely, as a dicentric. This may imply that a reversion of the centromere inactivation occurred or that the dicentric persisted long enough to produce both pseudodiccntric lines.…”
Section: Discussionmentioning
confidence: 92%
“…In one study alone, there were 25 individuals de scribed with tdic chromosomes resulting from the translocation between two acro centric chromosomes f976). Including the present case, there are only eight individuals described with tdic chromosomes consisting of one D-or G-group chromosome and another nonacrocentric autosome (SObrt et al, 1971 ;N iebuhr, 1972c;Warburton et al, 1973;NAKAGOMEetal., 1976;Skovby and N iebuhr, 1976;Roberts et al, 1977). There is one report of an individual with a tdic(6; 19) chromosome; this does not include either a D-or G-group chromosome (Pai.i.ister et al, 1974).…”
Section: Discussionmentioning
confidence: 78%
“…Most of the reports of tdic chromosomes showing one morphologic centromere indicate that the same centro mere is consistently constricted from cell to cell within the same individual (table I). In five of the previous reports of tdic chromo somes consisting of an acrocentric chromo some and a nonacrocentric chromosome, the centromeric region only on the nonacro centric chromosome showed a constriction (Subri et al, 1971;N iebuhr, 1972c;Warburion et al, 1973;Nakagomi et al, 1976;Roberts et al. 1977).…”
Section: Discussionmentioning
confidence: 92%
“…This has been seen in dicentrics consisting of two acrocentrics [Jenkins et al, 1981;Lucas et al, 1986], in dicentrics consisting of non-acrocentrics [Drets and Therman, 1983], and in dicentrics consisting of an acrocentric and a non-acrocentric [Niebuhr, 1972;SinghKahlon et al, 1977;Dewald et al, 1979;Uehara and Kida, 1986;Garcia-Esquivel et al, 1987]. Of the five acrocentric/non-acrocentric cases reported, three involved chromosome 18 [Singh-Kahlon et al, 1977;Uehara and Kida, 1986;Garcia-Esquivel at al., 1987].…”
Section: Discussionmentioning
confidence: 97%